Tryptophan-producing bacteria to mitigate osteoporosis and intestinal dysfunction - Bo Tian; Heng Wang; Yue Zhang; Jinmin Lv; Dongxiao Li; Chenmeng Zhou; Jialu Xu; Yichao Ni; Bingbing Wu; Mingchao Zhang; Huaxing Dai; Fang Xu; et al. (Bioactive Materials, 2025)
The relationship between gut microbiota and host health and disease is intricate, with microbiota-derived metabolites playing a crucial role in the gut-organ axis. In this study, we observe significantly decreased levels of microbial metabolites, particularly tryptophan derivatives in osteoporosis mice. Loss of tryptophan induced intestinal epithelial barrier dysfunction which compromised intestinal barrier integrity, leading to bone inflammatory responses and pathological osteoporosis. Through supplementation of tryptophan-producing bacteria, we effectively repair damaged intestinal barriers in colitis mice and mitigate bone loss, indicating the link between chronic colitis and osteoporosis. This approach offers a promising synthetic biology-based strategy to improve osteoporosis therapy by targeting gut tryptophan. This intervention also alleviates age-related osteoporosis in an aged mouse model, providing a potential therapeutic avenue for combating osteoporosis, a disease of growing concern in aging populations.